KUALITAS PELAYANAN PUBLIK DI KANTOR SISTEM ADMINISTRASI MANUNGGAL SATU ATAP - Hasan, Puput; Razak, Andi Rosdianti; Ma'ruf, Adnan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to describe the quality of service at the Makassar City One-Stop Manunggal Administration System (SAMSAT) Office. The type of research is qualitative research. Informants in this research collected data using interviews, observation and documentation. The research results show that the quality of motor vehicle tax services at the Makassar City SAMSAT office seen from five dimensions, namely: tangible, reliability, responsiveness, assurance and empathy, is good. Makassar City SAMSAT has responded to taxpayer complaints when problems occur in the service process, has knowledge of the work they do and shows good cooperation in serving and being friendly and polite in providing services to taxpayers, they serve with a smile and speak good words so that taxpayers feel appreciated.